(untitled) (Texas Journal of Medical Science, 2022)
The aim of this case report is to disclose atypical manifestations of non-epileptic seizures caused by cerebral ischemia as a result of a progressively large infected second branchial cyst compressing over the carotid bifurcation for the past three years. A female patient who presented to our clinic with symptoms of a constantly growing neck mass, pain, headache, difficulty turning the head, convulsions, teeth clenching, and syncope as a result of delayed appropriate treatment. After taking a thorough history of her signs and symptoms, along with laboratory tests and an electroencephalogram (EEG), we come to the definite diagnosis of the reason for her seizure-like symptoms, which were caused by the pressure exerted by the enlarged, infected second branchial cyst.